The Effect of Total Quality Management on Service Quality in the Context of Services Based Small and Medium Enterprises of Pakistan - DR. SAIMA BATOOL; YASIR KHAN; MUHAMMAD TAHIR (Journal of Business & Tourism, 2021)
Pakistani economy is making a transition from strong manufacturing base to the services and in this scenario, service based small and medium enterprises (SMEs) are playing a major role. In current study, we focus on total quality management (TQM) which has the potential to enable the service based SMEs to improve their competitiveness in current highly dynamic environment. The objective of the study was to assess the current level of TQM implementation and its effects on the service quality in the context of service based SMEs of Pakistan. A survey was designed to collect primary data and the measures for TQM and service quality were adapted from previous sources. The study utilized quantitative approach and through stratified random sampling, data is collected from 135 participants belonged to the management of SMEs located in three cities of Pakistan. Our findings indicate that the dimensions of TQM including top management commitment, customer focus, people management, supplier quality management, continuous improvement, and the process management are only moderately followed by the Pakistani service based SMEs. In terms of effects, three out of six TQM dimensions are having positive and significant effects on the service quality and together these TQM dimensions explain up to 60.7% change in the dependent variable of service quality. Based on the findings, we recommend that service based SMEs should give more attention to the TQM implementation